Association between clinical and salivary microbial parameters during orthodontic treatment with removable appliances with or without use of fluoride mouth rinse - Zingler, Sebastian; Pritsch, Maria; Lux, Christopher J. (European journal of paediatric dentistry, 2016)
AIM: To evaluate the correlation between clinical and salivary microbial parameters during treatment with removable orthodontic appliances with or without use of fluoride mouth rinse. MATERIALS AND METHODS: A group of 48 patients completed this randomized, controlled, parallel-group, clinical pilot study. 24 patients of the test group (TG) rinsed after tooth brushing with a fluoride mouth rinse (100 ppm AmF/150 ppm NaF) while 21 patients of the control group (CG) did not. Clinical parameters [Approximal Plaque Index (API), Papillary Bleeding Index (PBI)] as well as levels of salivary mutans streptococci (MS) and lactobacilli (LB) were assessed at baseline and after 3, 6, 9 and 12 months. Compliance was documented by participants. Appliance wear-times were estimated retrospectively by the patients. All participants received the same brushing instructions and were supplied with the same toothbrush/toothpaste. RESULTS: A significant correlation of API values with MS levels (p=0.0003) or with LB levels (p=0.001) was observed. Furthermore, appliance wear-times were significantly associated with API values (p=0.02). The changes of MS or LB levels between beginning and end of the study did not differ significantly between study groups. The changes of the API scores showed slightly different median values (-3.5 in the TG vs. 0 in the CG), the difference, however, was not significant. CONCLUSIONS: The results emphasise the need for a careful monitoring of the oral hygiene status in patients with removable orthodontic appliances. Larger controlled clinical trials are necessary to investigate treatment options such as use of supplementary fluoride mouth rinse.